2007
DOI: 10.1152/ajpheart.00291.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor-1 via prolyl-4 hydoxylase-2 gene silencing attenuates acute inflammatory responses in postischemic myocardium

Abstract: Natarajan R, Salloum FN, Fisher BJ, Ownby ED, Kukreja RC, Fowler AA 3rd. Activation of hypoxia-inducible factor-1 via prolyl-4 hydoxylase-2 gene silencing attenuates acute inflammatory responses in postischemic myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…HIF-1a expression is increased in hypoxaemic and inflamed tissues, and in many tumour tissues HIF-1a is known to promote tumour angiogenesis [32]. In contrast, no diseases have so far been described that are characterised by a decrease of tissue levels of the HIF-1a protein, with the exception of acute ischaemia and reperfusion of the myocardium [33,34] and the respiratory distress syndrome in pre-term lambs [35]. Decreased or impaired activity of this transcription factor has profound consequences for the homeostatic control at the cellular and mitochondrial level and will probably affect apoptosis and cellular senescence which characterise pulmonary emphysema [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1a expression is increased in hypoxaemic and inflamed tissues, and in many tumour tissues HIF-1a is known to promote tumour angiogenesis [32]. In contrast, no diseases have so far been described that are characterised by a decrease of tissue levels of the HIF-1a protein, with the exception of acute ischaemia and reperfusion of the myocardium [33,34] and the respiratory distress syndrome in pre-term lambs [35]. Decreased or impaired activity of this transcription factor has profound consequences for the homeostatic control at the cellular and mitochondrial level and will probably affect apoptosis and cellular senescence which characterise pulmonary emphysema [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…37 More recently, specific PHD2 silencing has been shown to enhance ventricular function and reduce infarct size in a mouse model of myocardial ischemia/reperfusion injury. 18,19 In the present study, we have developed a therapeutic strategy that promotes the local and transient inhibition of PHD1, PHD2, or PHD3. We demonstrated that PHD gene silencing promoted therapeutic revascularization in mice with hindlimb ischemia, with PHD3 attenuation leading to a better effect than similar reduction of PHD2 or PHD1.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, intraperitoneal injection of small interfering PHD (siPHD) upregulates cardiac inducible nitric oxide synthase expression, increases ventricular function, and reduces infarct size in a mouse model of myocardial ischemia/reperfusion injury. 18,19 In the present study, we used short hairpin RNAs (shRNAs) to downregulate murine PHD1, PHD2, or PHD3 levels and analyzed their efficiency as a therapeutic strategy in a model of mice hindlimb ischemia.…”
Section: Clinical Perspective On P 59mentioning
confidence: 99%
“…Targeting and scrambled siRNA were purchased from Santa Cruz. We used a previously validated approach of high-dose (0.45 mg/kg) systemic (intraperitoneal) injection mixed with an equal volume of siPORT amine (Ambion) in the live animal (35,36). For both cryopyrin and P2X7 a dose of 0.45 mg/kg induced a significant >80% reduction in target protein at 24 h. We then used this approach in the AMI model by administering the siRNA 24 h before surgery and then again every 72 h. Silencing efficacy was evaluated by WB using an anti-cryopyrin polyclonal antibody (Santa Cruz) and an anti-P2X7 polyclonal antibody (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%